Emerging technologies for shelf-life enhancement of fruits - Dar, Basharat Nabi; Mir, Shabir Ahmad (Oakville, ON ; Palm Bay, Florida : Apple academic Press, 2020)
"Focusing on new technological interventions involved in the postharvest management of fruits, this volume looks at the research on new and emerging techniques to maintain the quality of fruits from farm to table. The volume looks at the factors that contribute to shortening shelf life and innovative solutions to maintaining quality while increasing the length of time fruit remains fresh, nutritious, and edible. The volume considers the different needs of the diversity of fruits and covers variety of important topics, including factors affecting the postharvest quality of fruits microbial spoilage decontamination of fruits by non-thermal technologies new kinds of packaging and edible coatings ozone as shelf-life extender of fruits Emerging Technologies for Shelf-Life Enhancement of Fruits considers the fundamental issues and will be an important reference on shelf-life extension of fruits. Highlighting the trends in future research and development, it will provide food technologists, food engineers, and food industry professionals with new insight for prolonging the shelf life of fruits"--
OCLC-licensed vendor bibliographic record.
Keywords: Fruit -- Postharvest technology; Fruit -- Quality; SCIENCE / General; TECHNOLOGY / Agriculture / General; TECHNOLOGY / Food Science